Differential Gene Expression and Withanolides Biosynthesis During in vitro and ex vitro Growth of Withania somnifera (L.) Dunal - Thorat, Sachin Ashok; Kaniyassery, Arya; Poojari, Poornima; Rangel, Melissa; Tantry, Shashikala; Kiran, Kodsara Ramachandra; Joshi, Manjunath B.; Rai, Padmalatha S.; Botha, Anna-Maria; Muthusamy, Annamalai (Frontiers in Plant Science, 2022)
Ashwagandha (Withania Somnifera L. Dunal) is a medicinally important plant with withanolides as its major bioactive compounds, abundant in the roots and leaves. We examined the influence of plant growth regulators (PGRs) on direct organogenesis, adventitious root development, withanolide biosynthetic pathway gene expression, withanolide contents, and metabolites during vegetative, and reproductive growth phases under in vitro and ex vitro conditions. The highest shooting responses were observed with BAP (2.0 mgL-1) + KIN (1.5 mgL-1) supplementation. Furthermore, BAP (2.0 mgL-1) + KIN (1.5 mgL-1) + GA3 (0.5 mgL-1) exhibited better elongation responses with in vitro flowering. Half-strength MS medium with IBA (1.5 mgL-1) exhibited the highest rooting responses and IBA (1.0 mgL-1) with highest fruits, and overall biomass. Higher contents of withaferin A (WFA) (~8.2 mgg-1 DW) were detected in reproductive phase, whereas substantially lower WFA contents (~1.10 mgg-1 DW) were detected in vegetative phase. CAS (P = 0.0025), SMT (P = 0.0059), and DXR (P = 0.0375) genes resulted in a significant fold change in expression during reproductive phase. The LC-MS analysis revealed metabolites that were common (177) and distinct in reproductive (218) and vegetative (167) phases. Adventitious roots cultured using varying concentrations of IAA (0.5 mgL-1) + IBA (1.0 mgL-1) + GA3 (0.2 mgL-1) exhibited highest biomass, and IAA (0.5 mgL-1) + IBA (1.0 mgL-1) exhibited highest withanolides content. Overall, our findings demonstrate the peculiarity of withanolide biosynthesis during distinct growth phases, which is relevant for large-scale production of withanolides.